The Iveagh Trust of Dublin: A Constructed Community, 1889-1939 - O'REILLY, CHLOE MICHELLE (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2019)
The Iveagh Trust, founded by Sir Edward Cecil Guinness (later Lord Iveagh) in 1890, was a philanthropic housing institution established for the ?amelioration of the condition of the poor labouring classes of Dublin?. It was founded during a period when philanthropic giving was a widespread practice that aimed to provide affordable, clean and structurally sound accommodation for the poorest of the working class. This thesis will provide the first comprehensive analysis of the Iveagh Trust in the first fifty years since establishment. Analysis is carried out through the prism of a ?social looking-glass?, as a microcosm of wider Dublin, from three standpoints ? structural, organisational and communal. It will demonstrate that such philanthropic housing institutions, founded in the late Victorian period, were not just about bricks and mortar. Instead, the Trust constructed a self-reliant community that has flourished into the present day. A focal point of this thesis is centred on the Trust?s objective of amelioration. A consideration into the physical development of the Trust, and its impact on Dublin?s landscape is imperative. Additionally, this thesis examines the Trust from an organisational vantage point, questioning how the Trust was administered and maintained. Furthermore, this research investigates the Trust from a communal perspective, examining the network of relationships that were formed as the Iveagh Trust community matured, along with community members? experiences and interactions with wider events of a political, social and economic nature. Researching the Iveagh Trust from these perspectives will reveal the intricacies of philanthropy, housing provision and communal life. Oftentimes, the history of philanthropic housing institutions of this period are written as precursors to the welfare state, as a cog in a progressive wheel that led to state provision of housing. In addition, the shortfalls of philanthropic housing providers such as the Iveagh Trust are highlighted in the historiography, maintaining that they were unable to solve the problem of housing the working classes entirely - an argument that further enhanced the argument for state-intervention. It is imperative to consider the Trust?s primary objective: to ameliorate, meaning to make better. Moreover, the history of philanthropic housing trusts has often been written within the context of wider issues of public health, poverty and urban development and growth. While these are necessary approaches to take, it is imperative that Victorian philanthropic housing providers are studied in their own right, detailing the part they played, however small, in ?ameliorating? the working class. Therefore, it is only by researching individual housing Trusts that the true essence of life within them can be unveiled. By examining the Iveagh Trust from the inside, with access to private records previously untouched, this thesis aims to challenge these approaches and demonstrate that the Iveagh Trust was more than just a provider of working class housing. The study of the Iveagh Trust is first and foremost the study of a community, and, with access to private records previously untouched, this analysis has been made possible.
APPROVED
Keywords: philanthropy; Iveagh Trust; Dublin; housing; community; class relations